Internet Use and Ethnic Heterogeneity in a Cross-Section of Countries - Sefa Awaworyi Churchill; Davidson Okai; Alberto Posso (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates the association between ethnic heterogeneity and information technology related outcomes such as internet access and internet use. We argue that the global digital divide, as measured by cross-country differences in internet access and use, could be explained by cross-country differences in ethnic heterogeneity. We use indices of ethnic and linguistic fractionalization as measures of ethnic heterogeneity. Using data on a cross-section of 93 countries, we find evidence of a negative association between ethnic heterogeneity and the use and access of internet. Thus, cross-country differences in the global digital divide can be explained by the levels of ethnic fractionalization. Other determinants of the digital divide include income, infrastructure, literacy level, level of urbanization and inequality.
Keywords: 330; ethnic diversity; digital divide; information inequality; internet